2020
DOI: 10.1515/zfw-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The politicization of research methods, illustrated in the case of plant closures

Abstract: This paper contributes to building better methods in economic geography by examining the coevolution of theory, methodology, and should read methodology, and the practice of research methods with the policy context. The paper suggests that debates about how economic geography defines its theoretical and methodological boundaries have not been sufficiently cognizant of the effects of policy engagement. It posits that the politicized contemporary context is aligning research practices to policy constituencies, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Rice (2010) stressed the need to acknowledge and negotiate the power relations in elite interviews while Faulconbridge (2012) suggested that close dialogue was a useful method for studying power relations. Weller (2020) discussed privacy, disclosure and ever-stricter research ethics protocols as challenges facing access to key informants and close dialogue.…”
Section: What Happened To Stylised Facts and Close Dialogue?mentioning
confidence: 99%
“…Rice (2010) stressed the need to acknowledge and negotiate the power relations in elite interviews while Faulconbridge (2012) suggested that close dialogue was a useful method for studying power relations. Weller (2020) discussed privacy, disclosure and ever-stricter research ethics protocols as challenges facing access to key informants and close dialogue.…”
Section: What Happened To Stylised Facts and Close Dialogue?mentioning
confidence: 99%